Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
skoro maja się przecinać to f(x) = g(x)
[tex]\frac{6}{x}=\frac{2}{x+4}[/tex]
mnożąc na krzyz
6(x+4) = 2*x
6x + 24 = 2x
6x - 2x = -24
4x = -24 /:4
x = -6
[tex]y=f(-6)=\frac{6}{-6} =-1[/tex]
Odpowiedź:
f(x) = 6/x , g(x) = 2/(x + 4)
założenie:
x ≠ 0 ∧ x + 4 ≠ 0
x ≠ 0 ∧ x ≠ - 4
Df: x ∈ R \ { - 4 , 0 }
6/x = 2/(x + 4)
6(x + 4) = 2x
6x + 24 = 2x
6x - 2x = - 24
4x = - 24
x = - 24/4 = - 6
f(- 6) = 6/(- 6) = - 6/6 = - 1
g(- 6) = 2/(- 6 + 4) = 2/(- 2) = - 2/2 = - 1
Wykres w załączniku